2013
DOI: 10.1111/cas.12291
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced downregulation of miR‐30c promotes epithelial‐mesenchymal transition in human renal cell carcinoma

Abstract: MicroRNAs (miRNAs), which negatively regulate protein expression by binding protein-coding mRNAs, have been integrated into cancer development and progression as either oncogenes or tumor suppressor genes. miR-30c was reported to be downregulated in several types of cancer. However, its role in human renal cell carcinoma (RCC) remains largely unknown. Here, we show that miR-30c is significantly downregulated in human RCC tissues and cell lines. We found that miR-30c downregulation could be induced by hypoxia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 30 publications
1
53
0
1
Order By: Relevance
“…Cells experiencing EMT can also reactivate stem cell-associated self-renewal programs, which suppose some degrees of plasticity (66). Several reports suggest that hypoxia promotes EMT in various cancer types, including prostate, breast, renal, pancreatic, myeloma, lung, ovarian, and squamous carcinoma (6,46,62,64,97,100,108). Experimental studies have revealed that the stabilization of HIF-1␣ by hypoxia can directly or indirectly stimulate the expression of several E-box-binding transcription factors known to regulate EMT, including TWIST1, ZEB2, and SNAIL (64,90,121,124), while discrepancies among models suggest context-dependent events.…”
Section: Effect Of Hypoxic Stress On Tumor Target Plasticitymentioning
confidence: 99%
“…Cells experiencing EMT can also reactivate stem cell-associated self-renewal programs, which suppose some degrees of plasticity (66). Several reports suggest that hypoxia promotes EMT in various cancer types, including prostate, breast, renal, pancreatic, myeloma, lung, ovarian, and squamous carcinoma (6,46,62,64,97,100,108). Experimental studies have revealed that the stabilization of HIF-1␣ by hypoxia can directly or indirectly stimulate the expression of several E-box-binding transcription factors known to regulate EMT, including TWIST1, ZEB2, and SNAIL (64,90,121,124), while discrepancies among models suggest context-dependent events.…”
Section: Effect Of Hypoxic Stress On Tumor Target Plasticitymentioning
confidence: 99%
“…High levels of VEGF, which can be secreted by RCC cells, promote the development of new blood vessels that associate with the tumour, and can also act in an autocrine manner to increase tumour cell migration and invasiveness 198 . miR-141, 200a, 200b and 200c) is among the most frequently downregulated group of mi RNAs in RCC [199][200][201][202][203] . This miRNA family and miR-30c are involved in the regulation of EMT [199][200][201][202][203] .…”
Section: (Fig 4) [Au: Ok?]mentioning
confidence: 99%
“…miR-141, 200a, 200b and 200c) is among the most frequently downregulated group of mi RNAs in RCC [199][200][201][202][203] . This miRNA family and miR-30c are involved in the regulation of EMT [199][200][201][202][203] . Their expression can be inhibited by TGFβ signalling, leading to reduced expression of ZEB1, ZEB2 and SIP1 (REFS 199,200,202), which transcriptionally repress E-cadherin and induce EMT 106,107 (FIG.…”
Section: (Fig 4) [Au: Ok?]mentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a class of non-coding RNAs with a length of ~22 nucleotides (7,8). They regulate gene expression post-transcriptionally by imperfectly binding with the 3'-untranslated region (3'UTR) of targeted messenger RNAs (mRNAs) to suppress translation or induce mRNA degradation (7).…”
Section: Introductionmentioning
confidence: 99%